Behavioral Interventions to Enhance Smoking Cessation: A Summary of the Current Evidence. (March 2015) - Ciccolo, Joseph T.; Busch, Andrew M.
In the United States, the rate of cigarette smoking has significantly declined over the past 2 decades, but much more work is needed, as almost 20% of adults still smoke and smoking continues to be the leading preventable cause of death. Furthermore, rates of smoking in certain subpopulations have remained relatively stable and have historically been neglected in smoking cessation research. Pharmacotherapy (both prescription and over-the-counter) and behavioral support are known to aid cessation, and their combination is more effective than either alone. There are significant barriers to access, use, and adherence, however, especially with pharmacotherapy. Therefore, the purpose of this review is to provide an update and overview of the numerous behavioral approaches that have been used to enhance smoking cessation. The research described can be classified into the type of approach used, the setting in which it is delivered, and the population targeted. Regardless of the classification, all the approaches attempt to provide smokers with the information, motivation, and behavioral skills thought to be necessary for achieving initial cessation and sustained abstinence. Recommendations for future research on behavioral smoking cessation are also included.